MATH SOLVE

3 months ago

Q:
# HELPThe table shows the solution to the equation |2x - 4 - 3 = 3:Step 1 |2x - 4 = -3 + 3Step 2 12x - 4 = 0Step 3 2x - A4 = 0Step 4 2x = 4Step 5 x = 2Which is the first incorrect step?Step 1Step 2Step 3Solution is correct

Accepted Solution

A:

Answer:Step 1. Step-by-step explanation:|2x-4|-3=3Step 1 is incorrect because, the |2x-4 it's should be the problem down is |2x-4|-3=3.|2x-4|-3=32x-4-3=3Add or subtract the numbers from left to right.-3+3=02x-4=0Add by 4 both sides of equation.2x-4+4=0+4Simplify.0+4=42x=4Divide by 2 both sides of equation.2x/2=4/2Simplify, to find the answer.4/2=2X=2 is the correct answer.Step 1 is the correct answer.